Creating and using educational resources to improve practical teaching in the Human Physiology subject on the bachelor's degree course in Physical Activity and Sports Sciences. Assessment of results - Olmos, Gemma; Ruiz-Torres, M Piedad; Calleros, Laura; Cortes, Maria Alicia; de Frutos, Sergio; Ospina, Rafael; Rodriguez-Puyol, Manuel (Revista de universidad y sociedad del conocimiento, 2014)
The need to advance towards a methodology that strengthens self-directed learning and competency development among students has become a key focus of university teaching in recent years. This focus has given rise to new methodological strategies that have been enhanced by the use of information and communication technologies (ICTs). Within the progress of these methodological strategies, the creation of educational resources that help to meet their objectives has become an important part of the work done by university lecturers. Along those lines, a group of lecturers in the Department of Physiology at the University of Alcala (UAH), Spain, has created a series of educational resources using visual online tools for practical teaching in the Human Physiology subject. These resources were used for the first time in the 2011/12 academic year in the Human Physiology subject, taught in the first year of the bachelor's degree course in Physical Activity and Sports Sciences. This article presents the resources created and the methodology used. The results obtained from their use are also assessed; these results refer to the students' satisfaction with the resources, and the contribution that the resources and the methodology made to the students' learning. A survey was conducted to ascertain the students' opinions, and a comparative analysis was performed of the grades obtained by the students in the practical part of the subject and their impact on the overall grade, and those obtained in the previous academic year when the resources had not been used. The results show that the students were satisfied with both the educational resources and the methodology used, and that there was a significant improvement in the grades obtained in comparison to the previous academic year.